2022
DOI: 10.3390/ijerph192416799
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fire Smoke Exposure on Firefighters’ Lung Function: A Meta-Analysis

Abstract: Firefighters are exposed to a range of harmful substances during firefighting. Exposure to fire smoke has been associated with a decrease in their lung function. However, the cause–effect relationship between those two factors is not yet demonstrated. This meta-analysis aimed to evaluate the potential associations between firefighters’ occupational exposure and their lung function deterioration. Studies were identified from PubMed, Web of Science, Scopus and Science Direct databases (August 1990–March 2021). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…The indicators used to assess COVID-19 KP were based on lessons learned from similar studies in the context of infectious diseases (Table 1). 19. All these variables were factored in to determine the knowledge and practice behaviors of firefighters surveyed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The indicators used to assess COVID-19 KP were based on lessons learned from similar studies in the context of infectious diseases (Table 1). 19. All these variables were factored in to determine the knowledge and practice behaviors of firefighters surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Career firefighters are expected to have received comprehensive training in emergency response including infection control and best practices. Previous studies have found that first responders are often faced with various challenges including working under an emerging threat environment, keeping up to date with growing information, the lack of available training and education, and changes in their daily work responsibilities [4,19,20]. Professional groups like firefighters need to have sustainable strategies to improve knowledge through continuing education that focuses on targeting emerging and reemerging infectious agents, while also including technologies with proven efficiency to protect patient and worker health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health impacts closely related to forest fire emissions are mortality and morbidity from cardiorespiratory causes. Note that the emissions released increase influence the onset of asthma and chronic obstructive pulmonary disease (COPD) (Barbosa et al, 2022;Youssouf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%